Implementation of a Fast Detector Using a Supervised Machine Learning And Gabor Wavelet Feature Descriptors. - Tusa Jumbo, Eduardo (United States, 2014)
The basic purpose of IEEE 127 is to serve as a guide to show preferred (steady-state) frequency and voltage ratings for primary power systems. A careful study, was accomplished by the Flight Vehicle Systems Integration Subcommittee. The attached tabulation gives recommended standard frequencies and voltages for all types of aerospace electric apparatus for which standards appear practical.
Keywords: PROCEEDINGS OF THE IEEE; GABOR WAVELET; PANEL DE SISTEMAS DE ENERGIA; ENERGIA ELECTRICA